Factors Affecting the Use of the Library by Lecturers at the Faculty of Education, Souphanouvong University - Kittikhoun, Vangvichit; Phannalath, Vikate; Yongye, Noulongxiong; Panmanivong, Thavone; Khammeleesaysue, Her; Chitthavone, Chantaluk; Lamphaiphanh, Ketsalinh; Phommanisone , Souksavanh; Keophasith, Vathsana (Souphanouvong University Journal Multidisciplinary Research and Development, 2015)
The objective of this study was to determine the extent to which various factors (facilities, collection, services and personal motivation) positively or negatively influenced lecturers’ use of the Souphanouvong University Faculty of Education library, and in turn, influenced their students’ use of the library. The population consisted of 51 Faculty of Education lecturers. The research instrument comprised a questionnaire with 12 closed and open-ended questions, and the return rate was high (86%). Facilities most important for lecturers to use the library more were internet or wifi connection (75%), air conditioning (61%) and computers with educational software (53%). Lecturers described the collection in their subject areas as ‘lacking’ (86%), not enough in Lao language’ (59%), or ‘old (52%), and they looked at most types of materials in the collection only occasionally. Those materials used most were books in Lao 64%, newspapers 35%, magazines and journals 34%, books in English 29% and books in Thai 24%. While 48% thought services were good or suitable, 20% suggested the need for longer library opening hours. Lecturers indicated that they normally got the information they needed for work from their personal computer (86%) or books in the department or that they owned (77%). Only 16% used the library more than three times a month. However, 87% said they would bring their students to the library if classes about library use were offered. Based on these results, recommendations from the researchers will help administrators and librarians make short-term and long-term plans for improving the library facilities, collection and services, and will encourage lecturers and students to make better use of the library. The effectiveness of the improvements will be tested using action research. Ultimately, this research will help SU Faculty of Education lecturers improve their teaching and research, and in turn, enable their students to develop greater information literacy and become better independent learners.